Immunotherapy Combined With Chemotherapy for Postoperative Recurrent Penile Squamous Cell Carcinoma: A Case Report and Literature Review - Li, Na; Xu, Tangpeng; Zhou, Zhen; Li, Ping; Jia, Guohua; Li, Xiangpan (Frontiers in Oncology, 2022)
Penile squamous cell carcinoma (SCC) is a rare malignant tumor in males with a poor prognosis. Currently, the primary treatment is surgery. Recurrent cases have limited treatment options after failed radiotherapy and chemotherapy. The therapeutic effect of immunotherapy in penile SCCs has not been reported. Tislelizumab, a new PD1 inhibitor, has shown a satisfactory impact in treating head and neck SCC and lung SCC combined with chemotherapy. However, there is currently no report on its efficacy in penile SCC. Here, a 76-year-old man with multiple enlarged inguinal lymph nodes 11 months after radical surgery for penile SCC was administered immunotherapy (tislelizumab) combined with chemotherapy (albumin paclitaxel plus nedaplatin) for 2 cycles. Pelvic Magnetic resonance imaging (MRI) showed that the multiple lymph nodes in the groin area disappeared. To our knowledge, this is the first case report of immunotherapy combined with chemotherapy showing promising results in recurrent penile SCC. It provides a basis for developing a new treatment option combining immunotherapy and chemotherapy, whose efficacy needs to be further evaluated in penile SCC.